SISTEM TRACER PAKET PADA UNIT PROCESSING CENTER POS INDONESIA (PERSERO) MENGGUNAKAN METODE TRAVELLING SALES PERSON PROBLEM - Dahlan Abdullah; Richki Hardi (Informatika Mulawarman : Jurnal Ilmiah Ilmu Komputer, 2013)
Traveling salesperson problem-TSP problem is an optimization problem to find the optimal way for the traveling salesman who wants to visit several cities, and returned to the original departure city. TSP is a difficult problem when viewed from the point of computing. Several methods have been used to solve these problems but until now not been found mangkus algorithms to solve them. The easiest way to solve TSP is to try all possible routes and find the optimal route. However, at the time of the very practical now required to complete an algorithm that quickly so that the TSP solution obtained near optimal solutions.